Early Outcomes in Targeted Muscle Reinnervation for Traumatic Amputations - Denton, Stephen R.; McBride, Conor; Hammond, Alexander P.; LoGiudice, Anthony J. (Journal of Reconstructive Microsurgery Open, 2023)
Background Traumatic amputees commonly experience residual limb pain (RLP) and phantom limb pain (PLP) which present major barriers to rehabilitation. An evolving treatment, targeted muscle reinnervation (TMR), shows promise in reducing these symptoms. While initial data are encouraging, existing studies are low power, and more research is needed to assess the long-term outcomes of TMR. We present the results of self-reported outcome surveys distributed to major-limb amputees more than 1 year post-TMR which were compared with similar data from a landmark randomized control trial for context.Methods Data was obtained from 17 adult traumatic amputees who were more than 1 year post-TMR using a numerical rating scale and the Patient-Reported Outcomes Measurement Information System survey tool. Results were compared with a 2019 randomized control trial by Dumanian et al which assessed TMR versus standard care (SC) after major limb amputation and demonstrated improvement in pain scores 1 year post-TMR.Results There was a statistically significant reduction in this cohort of TMR amputees' RLP worst pain scores relative to the comparison study's SC amputees (without TMR). In general, there was no significant difference in outcomes between TMR cohorts. However, PLP worst pain was significantly higher in this cohort relative to the comparison study's TMR group.Conclusion These findings support the use of TMR for reducing RLP in traumatic amputees. Relative to a similar group treated without TMR in the comparison study, this cohort's RLP was significantly improved. Future studies should aim to recruit more amputees to allow for analysis of functional outcomes, especially in upper limb amputees.
Keywords: targeted muscle reinnervation; phantom limb pain; residual limb pain